Study of Sociology in Jurisprudence of Women's Leadership - Nurul Mahmudah; Supiah Supiah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2018)
This paper was made to analyze sociological studies in women's leadership fiqh. The results of the analysis of the author that the existence of matters relating to women's responsibilities exist from social, social and social factors in the community itself. If there is an ancient society, it cannot be a part of various aspects, intellectual and ability, for example. This cannot be applied again in the current social conditions of the community, where many women have had the highest education, in many cases even more, men are there, this happens for the broadest for women to be a leader.